Associations and mediators between types of motorcycle ownership and road traffic injuries among motorcycle taxi drivers in Dar es Salaam, Tanzania. (June 2023) - Francis, Filbert; Möller, Jette; Moshiro, Candida; Kiwango, George; Yngve, Berg Hans; Hasselberg, Marie
Highlights: Co-ownership or rental of motorcycles was associated with an elevated risk of RTIs. Long working hours significantly mediate the association of the risk of RTIs among co-owned motorcycle taxi drivers. Risky driving behaviours mediated the associations of the risk of RTIs among rented motorcycle taxi drivers. Abstract: Background: Rapid growth in the use of motorcycle taxis in low-and-middle-income countries has been associated with an increased risk of road traffic injuries (RTIs). This study aimed to examine the association between types of motorcycle ownership, such as self-ownership, rental or shared ownership, and the risk of RTIs among Tanzanian motorcycle taxi drivers. Furthermore, we investigated whether the risky driving behaviours, number of working hours and motorcycle conditions mediate the association between types of motorcycle ownership and risk of RTIs. The study included 164 cases of motorcycle taxi drivers with RTIs resulting in hospitalisation and 400 controls of motorcycle taxi drivers randomly selected from parking stages. The results show that motorcycle taxi drivers who co-own or rent their motorcycles were two to three times more likely to have RTIs than those who self-own their motorcycles after adjusting for age, education, marital status and the number of dependents. Mediation analysis shows that risky driving behaviours have a greater indirect effect on the risk of RTIs among motorcycle taxi drivers who rent their motorcycles, while the number of working hours had a significantly higher mediation effect on the risk of RTIs among motorcycle taxi drivers who co-own their motorcycles. This study shows that co-ownership or rental of motorcycles is associated with a higher risk of RTIs. Risky driving behaviours and the number of working hours are found to be important mediators. Further research on tailored approaches to improve and promote the safety of motorcycle taxi drivers' working conditions is needed.